Assessment of ionising radiation exposure of the staff and roommates from the cancer palliatively treated by QuadrametTM with Sm-153 - Kowalska, Aldona; Żórawska, Anna (Contemporary Oncology/Współczesna Onkologia, 2002)
Quadramet TM is a radiopharmaceutic including Sm-153 applied in the osseous pain caused by cancer metastasis. Quadramet is effective and in some cases the only agent used in palliative treatment in a view of its specific property as: - a short physical half life, - possibility of administer of high doses, - adequate type and radiation energy - relatively low toxicity. High emission of radiant energy of Quadramet can inspire fears considering the size of exposure of staff and roommates. In order to assess this value the dosimetry measurements were carried out, which gave the real picture of the exposure. In this paper the results of the measurements and conclusions are presented.